One-step reduced/quinone functionalized graphene oxide as reagentless lactate biosensing platform - Bravo, Iria; Revenga-Parra, Monica; Weber, Karina; Popp, Juegen; Pariente, Felix; Lorenzo, Encarnacion (Sensors and Actuators B-Chemical, 2018)
One-step approach to simultaneously reduce and modify graphene oxide (GO) using N,N’-Bis(3,4-dihydroxybenzylidene)-1,2-diaminobenzene Schiff base ligand (3,4DHS), in order to obtain functionalized reduced graphene oxide (rGO-DHS), is described. Once the novel hybrid nanomaterial was characterized by spectroscopic and electrochemical techniques, confirming the presence of the characteristic quinone/hydroquinone moieties, it has been combined with lactate oxidase (LOx) to develop a sensitive and selective reagentless lactate biosensor. The resulting biosensing device shows a very good analytical performance with detection and determination limits of 2.9 and 9.7 μM, respectively. The RSD for three different devices was lower than 9%. The operational stability is more than one month. The applicability has been demonstrated by the direct determination of the L-lactate content in white wine.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Functionalized reduced graphene oxide; Lactate determination; Lactate oxidase; Reagentless lactate biosensor